(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The effectiveness of learning is a state that shows how a focused or planned activity can be carried out properly and achieved. This is an absolute requirement that should be tried in all things and all conditions, especially during the Covid-19 pandemic. This study aims to find out the online learning process in Islamic Religious Education materials in MAN 3 Jombang during the covid-19 pandemic or the Implementation of Distance Learning. The benefit of this research is to provide a broad picture of the influence of online learning on the effectiveness of learning. The results of this study show that the effectiveness of learning in MAN 3 Jombang does not reflect good quality, due to the limitations of available facilities and connection facilities.